Role of Antiplatelet Therapy and Anticoagulation in Nonischemic Cardiomyopathy. Issue 5 (September 2016) - Carazo, Matthew; Berger, Jeffrey S.; Reyentovich, Alex; Katz, Stuart D.
Abstract : Heart failure continues to be a leading cause of morbidity and mortality throughout the United States. The pathophysiology of heart failure involves the activation of complex neurohormonal pathways, many of which mediate not only hypertrophy and fibrosis within ventricular myocardium and interstitium, but also activation of platelets and alteration of vascular endothelium. Platelet activation and vascular endothelial dysfunction may contribute to the observed increased risk of thromboembolic events in patients with chronic heart failure. However, current data from clinical trials do not support the routine use of chronic antiplatelet or oral anticoagulation therapy for ambulatory heart failure patients without other indications (atrial fibrillation and/or coronary artery disease) as the risk of bleeding seems to outweigh the potential benefit related to reduction in thromboembolic events. In this review, we consider the potential clinical utility of targeting specific pathophysiological mechanisms of platelet and vascular endothelial activation to guide clinical decision making in heart failure patients.